Compassionate Management of Mental Health in the Modern Workplace - Quelch, John A. (Springer International Publishing, 2018)
This proactive guide brings the relationship between work life and mental well-being into sharp focus, surveying common challenges and outlining real-life solutions. The authors' approach posits managers as the chief mental health officers of their teams, offering both a science-based framework for taking stock of their own impact on the workplace and strategies for improvement. Areas for promoting mental wellness include reducing stress and stigma, building a safe climate for talking about mental health issues, recognizing at-risk employees, and embracing diversity and neurodiversity. Emphasizing key questions to which managers should be attuned, the book speaks to its readers-whether in corporate, nonprofit, start-up, or non-business organizations-as a friendly and trusted mentor. Featured in the coverage: · Mind the mind: how am I doing, and how can I do better? · Dare to care: how are my people doing, and how might I help? · Building blocks for mental health: how do I manage my team? · Stress about stressors: what is constantly changing in the environment? · Changing my organization and beyond: how can I have a greater impact? Compassionate Management of Mental Health in the Modern Workplace holds timely relevance for managers, human resources staff, chief medical officers, development heads in professional service firms, union or employee organization leaders, legal and financial professionals, and others in leadership and coaching positions. "Workplace mental health: Wow! A subject that frightens most managers. If they read this book, they will strengthen their own skills and transform their workplace and our society." Donna E. Shalala, Trustee Professor of Political Science and Health Policy, University of Miami; former U.S. Secretary of Health and Human Services "Mental health is an underappreciated, and oft-misunderstood challenge that is growing in the modern workplace. This book provides leaders with practical advice to address mental health challenges in their organization and improve productivity and wellbeing. This is a topic that can no longer be ignored by leaders in any field, and a book that will fundamentally change the way we think about and help improve mental health in the workplace." Dominic Barton, Managing Director, McKinsey & Company .